An Easy Access to Sulfur Derivatives of 6,8-Dioxabicyclo[3.2.1]octanes, Naturally Abundant Scaffolds - Schmidt, Elena Yu.; Bidusenko, Ivan A.; Ushakov, Igor A.; Protsuk, Nadezhda I.; Trofimov, Boris A. (Synthesis, 2018)
Sulfur derivatives of 6,8-dioxabicyclo[3.2.1]octanes related to a number of natural products have been synthesized by the click hydrothiolation (AIBN or UV irradiation) of 7-methylene-6,8-dioxabicyclo[3.2.1]octanes, assembled from acetylene and ketones in a one-pot transition-metal-free synthetic operation. An unusual feature of this free-radical reaction is that it is accelerated in the presence of bases due to involvement of the latter in a competition between the thiol addition and proton-catalyzed isomerization of the starting bicyclooctanes.
Keywords: 6,8-dioxabicyclo[3.2.1]octanes; thiols; vinyl ethers; hydrothiolation